STH-CFD Codes Coupled Calculations Applied to HLM Loop and Pool Systems. (9th October 2017) - Angelucci, M.; Martelli, D.; Barone, G.; Di Piazza, I.; Forgione, N.
Abstract : This work describes the coupling methodology between a modified version of RELAP5/Mod3.3 and ANSYS Fluent CFD code developed at the University of Pisa. The described coupling procedure can be classified as "two-way, " nonoverlapping, "online" coupling. In this work, a semi-implicit numerical scheme has been implemented, giving greater stability to the simulations. A MATLAB script manages both the codes, oversees the reading and writing of the boundary conditions at the interfaces, and handles the exchange of data. A new tool was used to control the Fluent session, allowing a reduction of the time required for the exchange of data. The coupling tool was used to simulate a loop system (NACIE facility) and a pool system (CIRCE facility), both working with Lead Bismuth Eutectic and located at ENEA Brasimone Research Centre. Some modifications in the coupling procedure turned out to be necessary to apply the methodology in the pool system. In this paper, the comparison between the obtained coupled numerical results and the experimental data is presented. The good agreement between experiments and calculations evinces the capability of the coupled calculation to model correctly the involved phenomena.